(untitled) (Revista de Medicina Clinica, 2020)
Currently we live in a time of demographic change in Mexico, and by 2050 we will already have a mature population with life expectancies greater than 80 years, therefore, we will face catastrophic diseases such as Vascular Cerebral Diseases and Dementias. The current term of vascular cognitive impairment was coined by the group of experts for the Vascular Impairment of Cognition Classification Consensus Study (VICCCS) and is currently divided into mild and severe vascular cognitive impairment, the severe being considered vascular dementia. This introspection article tries to clarify similar concepts between EVCs and dementias, in order to establish prevention guidelines that can modify the dementia incidence.